Protection of Creditors’ Rights and Minority Shareholders in the Company Dissolution Process Based on Indonesian Positive Law - Ratnawati, Iis; Mardikaningsih, Rahayu; Halizah, Siti Nur (Journal of Social Science Studies, 2024)
This study analyses the regulations governing the dissolution of companies and the mechanisms for distributing assets to creditors, as well as the protection of the economic rights of minority stakeholders under Indonesian positive law. Based on a normative legal literature study, it examines the harmonization between Law No. 40 of 2007 on Limited Liability Companies and Law No. 37 of 2004 on Bankruptcy and PKPU. It emphasizes the mechanism of payment order through liquidation or bankruptcy and the pari passu prorate parted principle that guarantees fairness among creditors. On the other hand, minority shareholders are protected both substantively in the form of residual rights after debt repayment and procedurally through appraisal rights, information, and access to remedies such as the cancellation of GMS decisions that are detrimental to them. This study highlights the importance of transparent governance and the active role of minorities in protecting their economic rights. The final conclusion affirms that the national positive law system has provided a comprehensive set of tools to deliver justice and legal certainty in corporate dissolution, although its success remains dependent on the quality of governance implementation and the integrity of legal actors.